Educational animal game for kindergarten - Tan, Yi Wen (2014)
With the advancement of digital technology in our world, the paradigm of learning has seen a massive changes with lot of effort and innovation are done in place to promote interactive learning. In this context, game based learning is introduced to promote interactive learning that provides a proper two way communication which is essential in ensuring the intended message is conveyed. Conventional learning materials such as books and newspapers lack interactivity that is essential in engaging as well as motivating students in striving to learn more. The delivery of information and knowledge through those conventional medium is static which requires no interaction or response from user, such scenario triggers a big question of student's understanding regarding the information that he/ she has read. Thus, a newer approach of teaching as well as motivating student in learning more should be introduced. As such, an educational game that demands cognition feedback from student that offers both interactivity and entertainment should be in place to assist the conventional learning material. In addition, with the introduction of an educational game, information and knowledge can be delivered in a crisp, visually powerful manner which could enhance student's understanding while assisting the digestion of information of the respective student.